PENERAPAN MEDIA PEMBELAJARAN BERBASIS ANDROID DENGAN SMART APPS CREATOR (SAC) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS VI SD - Kurniawan, Bayu; Ahmad Muhibbin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The significance of Pancasila Education in elementary schools as the initial foundation for the development of noble character and the application of Pancasila values in the early stages for any individual. In addition, Pancasila education also instils in the younger generation a sense of affection for the homeland and the ability to serve the nation in the future. For this reason, educators are crucial in the delivery of Pancasila education in a manner that is both engaging and meaningful. This investigation is designed to evaluate the efficacy of Android-based learning media, specifically Smart Apps Creator (SAC), in enhancing the learning outcomes of Pancasila education among sixth-grade elementary school students. This study employs descriptive statistical analysis as its research methodology. Data obtained from pre-tests and post-tests will be subjected to descriptive statistical analysis. In an effort to substantiate the efficacy and advantages of employing SAC learning media, data from interviews and observations will be presented. The results of this study suggest that sixth-grade elementary school students in Pancasila Education can significantly enhance their academic performance through the use of SAC learning media. Furthermore, this investigation determined that using SAC learning media can improve students' motivation and engagement in the learning process.